Male-specific roles of lincRNA in C. elegans fertility - Shabtai, Reut; Tzur, Yonatan B. (Frontiers in Cell and Developmental Biology, 2023)
The testis is the mammalian tissue with the highest expression level of long intergenic non-coding RNAs (lincRNAs). However, most in vivo models did not find significant reductions in male fertility when highly expressed lincRNA genes were removed. This suggests that certain lincRNAs either act redundantly or lack functional roles. In the genome of the nematode Caenorhabditis elegans, there is an order of magnitude fewer lincRNAs genes than in mammals, making it an ideal model to test these possibilities while lowering the potential for redundancy. We identified five highly and dynamically expressed lincRNAs in male C. elegans gonads and quantified the fertility of worm strains in which these genes were removed. Smaller brood sizes were observed in three of the lincRNA-deleted strains, demonstrating reduced male fertility in worms with those genes removed. This stands in contrast with the hermaphrodites, in which no significant reductions of broods were observed in deletion strains. Interestingly, the reduced brood was significant only in the last days of egg laying in two of these strains, suggesting the effect is due to either a smaller number or early aging of the transferred sperm. We detected a mild increase in embryonic lethality in only one of the strains, supporting the possibility that these lincRNAs do not affect fertility through critical roles in essential meiotic processes. Together our results indicate a sexually dimorphic outcome on fertility when lincRNA are removed and show that, unlike mammals, individual lincRNAs in C. elegans do play significant roles in male fertility